Signs of current suicidality in men: A systematic review. - Tara Hunt; Coralie J Wilson; Peter Caputi; Alan Woodward; Ian Wilson (PLoS ONE)
Suicide signs have been identified by expert consensus and are relied on by service providers, community helpers' and family members to identify suicidal men. Whether signs that are reported in suicide literature accurately describe male presentations of suicidality is unclear. A systematic review of the literature was conducted to identify male-specific signs of current suicidality and identify gaps in the literature for future research. Searches through Medline, CINAHL, PsychInfo and the Behavioral Sciences Collection, guided by the PRISMA-P statement, identified 12 studies that met the study eligibility criteria. Although the results generally reflected suicide signs identified by expert consensus, there is little research that has examined male-specific signs of the current suicidal state. This review highlights the need for scientific research to clarify male presentation of suicidality. Implications for future research to improve the prompt identification of suicidal men are discussed.